Dampak Institusi pada Penerapan Teknologi Pertanian Mina Padi terhadap Pengembangan Kapabilitas Petani sebagai Prakondisi Kesejahteraan (Studi Kasus Kelompok Tani di Dusun Samberembe Desa Candibinangun Kecamatan Pakem) - Fatma Nurfera (EXERO : Journal of Research in Business and Economics, 2020)
This study aims to analyze the impact of institutions towards the application of agricultural technology to farmer capabilities’ development. The utilization of agricultural technology is commonly viewed as an appropriate way to develop agricultural sector, particularly to empower smallholder farmers. Nevertheless, practically, the degree of successful application of a technology depends on certain preconditions. One of such preconditions is institution. This study attempts to analyze a case of an agricultural setting with a technology application at Samberembe, Candibinangun, Pakem. Data collection is conducted through interviews, observation, and documental study. The interviewees are mina padi farmers, farmer group leader, agricultural instructors, village apparatus, and agricultural activists. The results show that the existence of institutions related to the case in one way ensures farmers’ capabilities development, but in another way gives a kind of barriers, particularly in the use of an agricultural technology, namely mina padi. Such institutional design, at the formal, provides opportunity for farmers to access three features i.e. the introduction of agricultural technology, a range of agricultural facilities, and farming trainings. All of these features simultaneously build a precondition for the farmers in achieving the wellbeing. Meanwhile, the existence of informal institutions that created from daily habits of the farmers in managing farm to some extent weakens the development of farmers’ knowledge and skills. Based on the study results, there is an opportunity for those who have authorities in the relevant domains of an agricultural technology application in order to improve the impact of the program by giving more concern to any particular conditions of the farmers, including their informal institution, rather than just applying the program without considering the actual condition of the related field.